Potensi Ekstrak Jahe (Zingiber officinale) sebagai Antibakteri Alami terhadap Kontaminasi Bakteri pada Petis Udang - Suci Fabilla; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Shrimp petis is a traditional Indonesian fermented product that is susceptible to contamination by pathogenic bacteria such as Staphylococcus aureus, Escherichia coli, and Pseudomonas spp. Preservation is generally carried out with chemical antibiotics, but their use can cause side effects and microbial resistance. This study aims to examine the effectiveness of ginger extract (Zingiber officinale) as a natural antibiotic against bacteria in shrimp petis. Ginger extract is known to contain active compounds such as gingerol and shogaol which have antibacterial activity. Through literature studies and disc diffusion method analysis, it was found that ginger extract was able to produce an inhibition zone of 12–22 mm against test bacteria. These results indicate that ginger extract is effective in inhibiting the growth of pathogenic bacteria and has the potential to be used as a natural preservative. In addition, a combination of biological, chemical, and natural preservation approaches is recommended to maintain the quality and safety of shrimp petis. The use of ginger extract is in line with the trend of healthy and environmentally friendly food.